What is the relationship between burnout and motivation to learn? - Ahmad Nazri, Nur Asyikin; Muhammad, Fadiatul Hasinah; Sheikh Suhaimi, Siti Nur Yasmin; Hasnor, Hanin Naziha; Saidin, Nurhafizah; Ngah, Suhaiza; Rahmat, Noor Hanim (HRMARS, 2023)
Academic achievement and the well-being of students are crucial factors in educational settings. In recent years, the phenomenon of burnout has gained significant attention due to its detrimental effects on individuals' mental health and overall performance. The purpose of this study was to explore learners' perceptions of their motivation and the causes of burnout among students in Malaysia. This quantitative study aimed to examine the motivation factors for learning among undergraduates in Malaysia. A purposive sample of 172 participants responded to the survey. The respondents were from two different institutions: Foundation students from two public universities. The instrument used was a 5-point Likert scale survey consisting of five components: value, expectancy, effectiveness, burnout and exhaustion, and burnout disengagement. These results suggest possible reasons for learners' perceptions of burnout by indicating that physical and emotional exhaustion is a common component of burnout experiences in the learning environment. Understanding these causes can help create strategies to reduce burnout and increase learners' motivation in the educational environment, as it sheds light on the relationship between burnout and motivation to study. The results also suggest a moderate positive relationship between burnout and the value components, burnout and expectancy, as well as burnout and affective components.